The ameliorating effect of uncooked beans diet in CD-1 mice - W, Aduema; JU, Agbai; AC, Wariso (Innovare Journal of Medical Sciences, 2019)
This study was therefore, designed to investigate the ameliorating effect of uncooked beans on pain sensation using three groups of Swiss white mice (control and test) weighing 20g-30g (n=10 each).The control group received normal rodent chow, while the test group received 15g of uncooked beans in 15g of rodent chow per day and serotonin precursor (5HTP) (0.2mg/15g w/w) diet. Water was given adlibitum while daily food and water intake, as well as body weight changes, were monitored during the 30-day study. The formalin tests were used to assess pain sensation. The results showed that in the formalin test, the frequencies and durations of paw licks and paw attention in both phases of the test was significantly lower (P< 0.05) compared to the control group. Therefore, consumption of uncooked Nigeran beans diet decreases pain sensation in mice.Â Â Â